Injury-Related Emergency Department Visits After Hurricane Maria in a Southern Puerto Rico Hospital. (February 2020) - Frasqueri-Quintana, Verónica M.; Oliveras García, Carene A.; Adams, Laura E.; Torres-Figueroa, Xiomara; Iriarte, Rafael Iván; Ryff, Kyle; Sánchez-González, Liliana; Pérez Gómez, Vivian; Pérez-Rodríguez, Nicole M.; Alvarado, Luisa I.; Paz-Bailey, Gabriela
ABSTRACT: Objective: The aim of this study was to describe individuals seeking care for injury at a major emergency department (ED) in southern Puerto Rico in the months after Hurricane Maria on September 20, 2017. Methods: After informed consent, we used a modified version of the Natural Disaster Morbidity Surveillance Form to determine why patients were visiting the ED during October 16, 2017–March 28, 2018. We analyzed visits where injury was reported as the primary reason for visit and whether it was hurricane-related. Results: Among 5 116 patients, 573 (11%) reported injury as the primary reason for a visit. Of these, 10% were hurricane-related visits. The most common types of injuries were abrasions, lacerations, and cuts (43% of all injury visits and 50% of hurricane-related visits). The most common mechanisms of injury were falls, slips, trips (268, 47%), and being hit by/or against an object (88, 15%). Most injury visits occurred during the first 3 months after the hurricane. Conclusions: Surveillance after Hurricane Maria identified injury as the reason for a visit for about 1 in 10 patients visiting the ED, providing evidence on the patterns of injuries in the months following a hurricane. Public health and emergency providers can use this information to anticipate health care needs after a disaster.